PEMBELAJARAN BERBEDA PADA EKSTRAKURIKULER TAHFIDZUL QUR’AN SISWA SMPN 2 KEMLAGI - Istikhoma, Wahyu; Rohmad, Muhammad Ali; Wachidah, Hajar Nurma (Yayasan Amanah Nur Aman, 2025)
Education does not only focus on academic aspects, but also has an important role in shaping the character and moral values of students. One form of character education in the religious field can be realized through Tahfidzul Qur'an extracurricular activities. However, the implementation of this activity at SMPN 2 Kemlagi often experiences several obstacles such as learning methods that are still monotonous and differences between students' interests and abilities in memorization that cannot be ignored. The research was conducted with the aim of describing the application of differentiated learning in extracurricular Tahfidzul Qur'an as well as identifying supporting and inhibiting factors in its application. This research used a qualitative method with a descriptive approach. Data were collected through observation, interviews and documentation, then analyzed through the stages of data reduction, data presentation and conclusion drawing. After in-depth analysis, the results show that the implementation of differentiated learning has been carried out effectively, by adjusting teaching strategies based on the readiness, interests and learning styles of each student. This is reflected in the learning practices carried out by the mentor teacher through the application of content, process and product differentiation. The factors that support success include student mapping, adequate facilities, and support from the school environment and parents. Meanwhile, obstacles that arise include time constraints, differences in ability and lack of motivation from some students.